Proximate Composition of Some Selected Browse Plants in Gombi Local Government Area, Adamawa State, Nigeria - D.I. Mojaba; D. Khobe; E Nelson (International Journal of Advances in Applied Sciences, 2016)
Twelve (12) indigenous browse plants harvested from four districts of Gombi Local Government, Adamawa State were evaluated for their proximate composition. The samples were randomly collected in the study and identified at the Forestry Department, Ministry of Agriculture, Adamawa State. The proximate composition of the collected samples was carried out at the Animal production Nutrition Laboratory of Adamawa University, Mubi. Parameters measured include dry matter (DM), crude fibre (CF), crude protein (CP), Ash (minerals). Nitrogen free extract (NFE) and ether extract (EE). Results obtained showed that DM ranged from 55.5%-80%, CF (23-68%), CP (7.88-19.25%), NFE (22.25-69.97%), EE (3.0-6.0%) and Ash (6.0-12.00%). The data obtained were used to determine the suitability of the browse plants species for ruminant animal production. Results revealed that nutrient contents in plant samples vary in composition.